Temperature and soil fertility as regulators of tree line Scots pine growth and survival—implications for the acclimation capacity of northern populations. (23rd November 2017) - Rousi, Matti; Possen, Boy J. M. H.; Ruotsalainen, Seppo; Silfver, Tarja; Mikola, Juha
Abstract: The acclimation capacity of leading edge tree populations is crucially important in a warming climate. Theoretical considerations suggest that adaptation through genetic change is needed, but this may be a slow process. Both positive and catastrophic outcomes have been predicted, while empirical studies have lagged behind theory development. Here we present results of a 30‐year study of 55, 000 Scots pine ( Pinus sylvestris ) trees, planted in 15 common gardens in three consecutive years near and beyond the present Scots pine tree line. Our results show that, contrary to earlier predictions, even long‐distance transfers to the North can be successful when soil fertility is high. This suggests that present northern populations have a very high acclimation capacity. We also found that while temperature largely controls Scots pine growth, soil nutrient availability plays an important role—in concert with interpopulation genetic variation—in Scots pine survival and fitness in tree line conditions. These results suggest that rapid range expansions and substantial growth enhancements of Scots pine are possible in fertile sites as seed production and soil nutrient mineralization are both known to increase under a warming climate. Finally, as the ontogenetic pattern of tree mortality was highly site specific and unpredictable, our results emphasize the need for long‐term field trials when searching for the factors that control fitness of trees in the variable edaphic and climatic conditions of the far North. Abstract : The acclimation capacity of leading edge tree populations is crucially important in a warming climate. Here we present results of a 30‐year study of 55, 000 Scots pine (Pinus sylvestris) trees, planted in 15 common gardens at and above the present Scots pine tree line. We show that even long‐distance transfers to the North can be successful when soil fertility is high suggesting very high acclimation capacity for present northern populations. While temperature largely controls Scots pine growth, soil nutrient availability plays an important role—in concert with interpopulation genetic variation—in Scots pine survival and fitness in tree line conditions.